International University Network Internet Project of Integrated Engineering Education - I. V. Breido; S. M. Stazhkov; A. V. Bobryakov; V. G. Khomchenko; A. A. Kabanov; B. Katalinic (Moscow Polytechnic University, 2019)
The transfer of educational technologies of the OECD countries for higher technical education in the CIS requires significant financial and material resources. It is advisable to unite pedagogical teams and the laboratory base of universities that train specialists in related specialties using the Internet. The international scientific and educational network Internet project "Synergy" has been implemented with the support of the concern "Festo" (Germany). The universities directly involved in the regular educational activities of the project are NIU Moscow Power Engineering Institute, Peter the Great St. Petersburg Polytechnic University, the Baltic State Technical University "VOENMECH" named after D.F. Ustinova, Omsk State Technical University and Karaganda State Technical University. The laboratories of the project participants are equipped with modern training stands and multimedia tools for conducting on-line courses and laboratory work in the remote access mode produced by the leading domestic and foreign companies including world leaders in the field of automation and robotics Festo, Siemens, Mitsubishi Auto Electrician.Regular online training has been organized with the use of exchange, composite and embedded module courses. The experience gained in the process of project implementation became the basis for the development of a new interdisciplinary program for the specialized magistracy as "Robotics. Control systems" for the Kazakhstan industry. The international university network project "Synergy" can become the basis for the practical implementation of the principles of the Bologna process, taking into account the specifics of the CIS countries.